Method for producing molded product
By applying surface roughness of at least 1.05 μm to the elastomer layer through an uneven transformed film, the sliding properties of molded products are improved while maintaining mechanical strength and durability.
Patent Information
- Application Number
- JP2024191526
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-04
AI Technical Summary
Existing elastomers used in molded products often exhibit excessive slipperiness due to smooth surfaces, compromising their sliding properties.
The surface of the elastomer layer is engineered to have a roughness of at least 1.05 μm by applying unevenness, which can be achieved through the use of an uneven transformed film during the molding process, transferring the surface irregularities to the elastomer layer.
This approach enhances the sliding properties of the molded product while maintaining or improving other rubber characteristics such as mechanical strength and durability.
Smart Images

Figure 2025016643000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a molded article. [Background technology]
[0002] Various studies have been conducted on elastomers that form molded articles. For example, the technology described in Patent Document 1 is known as this type of technology. Patent Document 1 describes an elastomer with a smoothed surface (Claim 1 of Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2011-073148 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, as a result of investigations by the present inventors, it was found that the elastomer described in Patent Document 1 above has room for improvement in terms of smoothness. [Means for solving the problem]
[0005] Further investigation by the present inventors has revealed that with ordinary elastomers, even if desired rubber properties are obtained, the surface is often formed to be smooth, and the slip properties are often reduced. As a result of further intensive research based on this knowledge, it was found that the slipperiness can be improved by imparting irregularities to the surface of the elastomer layer, which led to the completion of the present invention.
[0006] According to the present invention, A molded article having an elastomer layer, A molded article is provided in which the elastomer layer has a surface roughness Ra of 1.05 μm or more on at least one side. Effect of the Invention
[0007] According to the present invention, there is provided a molded article having an elastomer layer with excellent slip properties. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 is a diagram illustrating a method for imparting irregularities to the surface of an elastomer layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The molded article of this embodiment includes an elastomer layer. In this molded article, the elastomer layer is configured so that at least one side thereof has a surface roughness Ra of 1.05 μm or more.
[0010] According to the findings of the present inventors, it was found that there is room for improvement in the slipperiness because the surface of a normal elastomer layer is composed of a smooth surface with a surface roughness Ra of about 0.5 μm. In response to this, it was found that the slipperiness can be improved by imparting irregularities to the surface of the elastomer layer, thereby making the surface roughness Ra 1.05 μm or more.
[0011] According to this embodiment, a molded article having an elastomer layer with excellent slip properties can be realized.
[0012] In addition, according to the findings of the present inventors, it has been newly discovered that when a coating layer is formed by coating the surface of an elastomer layer with a silicone-based lubricant or the like, by setting the surface roughness Ra to 1.05 μm or more, the lubricity is improved, but rubber properties such as elongation at break, tensile strength, and hardness are reduced. Here, examples of a technique for coating the surface of an elastomer with a silicone-based lubricant to improve lubrication include paragraphs 0031 and 0048 described in JP 2017-165978 A.
[0013] After considering this trade-off between slipperiness and rubber properties, the researchers discovered that by physically imparting irregularities to the surface of the elastomer layer, it is possible to improve slipperiness while suppressing a deterioration in the rubber properties. Although the detailed mechanism is unclear, it is believed that the slipperiness is improved without deteriorating the rubber properties because no coating layer made of a slip-imparting agent is formed, and the surface (exposed surface) is left uncoated without any coating layer formed, while still being able to be moderately roughened.
[0014] In the molded article of this embodiment, the surface of the elastomer layer is composed of an exposed surface having surface irregularities, and is configured so that the surface roughness Ra of the surface of the elastomer layer is 1.05 μm or more.
[0015] According to this embodiment, a molded article having an elastomer layer with excellent slip properties and rubber characteristics can be realized.
[0016] The elastomer layer according to the present embodiment can have a surface unevenness imparted (transferred) during molding of the elastomer using, for example, an unevenness transfer film. That is, the surface unevenness can be imparted by transferring the surface unevenness of the unevenness transfer film to the surface of the elastomer layer.
[0017] Here, an example of a method for imparting irregularities to the surface of an elastomer layer will be described with reference to Fig. 1. Fig. 1 shows a cross-sectional view of a press molding process using a mold.
[0018] As shown in FIG. 1, an upper mold 10 and a lower mold 20 are combined to form a molding space. In this molding space, the concave-convex transfer films 30, 40 and an elastomer 50 are placed. Then, by performing press molding under a predetermined heating and pressure condition, the surface profile (surface concave-convex shape) of the surface 32 of the concave-convex transfer film 30 can be transferred to the surface 52 of the sheet-like elastomer 50 (elastomer layer). At this time, the surface concave-convex shape of the concave-convex transfer film 40 can also be transferred to the opposite side of the elastomer 50. It is also possible to form a surface concave-convex shape on the lower mold 20 and transfer it without using the concave-convex transfer film 30. The concave-convex transfer films 30, 40 may be placed on both sides of the elastomer 50, or the concave-convex transfer film 30 may be placed on one side of the elastomer 50.
[0019] The molding method is not particularly limited, but for example, compression molding, transfer molding, injection molding, etc. can be used.
[0020] The unevenness transfer films 30 and 40 can be disposed so as to contact at least a part or the entire surface of the elastomer 50 . The unevenness transfer films 30 and 40 may be, for example, a resin sheet such as a matte film or sandpaper (sand mat), or a metal sheet having an uneven surface. The unevenness transfer films 30 and 40 may be the same or different.
[0021] The matte film is a resin sheet in which particles are kneaded into the resin, while the sandpaper (sand mat) is a resin sheet in which the surface is subjected to a blasting treatment such as spraying sand (silica sand) to impart fine irregularities to the film surface.
[0022] The material of the unevenness transfer film 30 is not particularly limited as long as it is a resin material that has excellent releasability from the material of the elastomer 50. For example, when the elastomer 50 is a silicone-based elastomer, the resin material of the unevenness transfer film 30 may be, for example, polyester (PE), polyethylene terephthalate (PET), polyvinyl alcohol (PVA), or the like. These may be used alone or in combination of two or more kinds.
[0023] The surface roughness Ra of the matte film is, for example, 1.0 μm to 100 μm, preferably 2.0 μm to 50 μm. The surface roughness of the sandpaper may be configured to be coarser than the surface roughness of the matte film. The mesh of the sandpaper is, for example, #100 to #10000, preferably #300 to #8000, more preferably #500 to #5000.
[0024] When measured using the method for measuring the surface roughness Ra of the elastomer layer described below, the surface roughness Ra of the unevenness transfer film 30, 40 is, for example, 1.0 μm or more, preferably 1.5 μm or more, more preferably 2.0 μm or more, and even more preferably 5.0 μm or more, or may be 100 μm or less, 50 μm or less, or 20 μm or less. Alternatively, instead of using the unevenness transfer films 30, 40, the mold surface of the upper mold 10 or the lower mold 20 that comes into contact with the elastomer 50 may be given a surface roughness Ra in such a numerical range. However, the use of the unevenness transfer films 30, 40 provides superior releasability, and therefore allows for the realization of an elastomer layer with superior manufacturing stability.
[0025] The elastomer 50 may be in a sheet form, but may be molded into various shapes depending on the application. At this time, the concave-convex transfer film 30 may be placed against a surface 52 of a suitable elastomer 50.
[0026] The molded article having the above-mentioned elastomer layer can be used for various purposes, and can be suitably used, for example, as a component part for medical equipment such as a gasket, for automotive applications, for construction applications, or as a cushioning material during molding.
[0027] The elastomer layer according to this embodiment will be described in detail below.
[0028] First, the characteristics of the elastomer layer will be described. The lower limit of the surface roughness Ra of the surface of the elastomer layer is, for example, 1.05 μm or more, preferably 2.0 μm or more, and more preferably 4.0 μm or more. This can enhance the slipperiness of the elastomer layer. On the other hand, the upper limit of the surface roughness Ra of the surface of the elastomer layer is, for example, 100 μm or less, preferably 50 μm or less, and more preferably 30 μm or less. This can maintain the mechanical hardness of the molded product.
[0029] The surface roughness Ra of the elastomer layer is measured using a Keyence VK-9700 laser microscope under the conditions of lens: magnification 20x, pitch: 0.2 μm. Next, the surface roughness Ra (μm) of the planar surface of the elastomer layer is measured under the conditions of measurement area: 300 μm × 300 μm in accordance with JIS B0601-2001 described in the analysis software VKanalyzer.
[0030] The upper limit of the tack peak value TP on the surface of the elastomer layer is, for example, 4.0N or less, preferably 3.0N or less, and more preferably 1.0N or less. By making it 4.0N or less, it is possible to improve the slipperiness to a degree that does not cause practical problems. Furthermore, by making it 1.0 or less, it is possible to realize good slipperiness even when the contact speed is high when the contact object is repeatedly contacted. On the other hand, the lower limit of the tack peak value TP is not particularly limited, but may be, for example, more than 0N or 0.1N or more.
[0031] The procedure for measuring the tack peak value TP is as follows. Area 150mm2 The flat surface of an aluminum probe having a flat surface of the above-mentioned test piece is brought into contact with the surface of the elastomer layer, which is the measurement sample, under conditions of a probe moving speed of 2.3 mm / sec, a probe crimping strength of 12 N, and a crimping time of 6 seconds, and the flat surface of the aluminum probe is then peeled upward at a probe moving speed of 2.3 mm / sec. The tack peak value on the surface of the elastomer layer is measured five times by a probe tack test, and the average of the five measured values is defined as the above-mentioned tack peak value TP.
[0032] The upper limit of the dynamic friction coefficient on the surface of the elastomer layer is, for example, 2.0 or less, preferably 1.5 or less, and more preferably 1.0 or less. This can improve the slipperiness of the elastomer layer. On the other hand, the lower limit of the dynamic friction coefficient is not particularly limited, but may be, for example, more than 0 or 0.1 or more. In this embodiment, the dynamic friction coefficient can be measured in accordance with JIS K7125, and is the dynamic friction coefficient against polypropylene (PP) which is assumed to be applied to a gasket.
[0033] The lower limit of the elongation at break of the elastomer layer according to the present embodiment, measured in accordance with JIS K6251 (2004), is, for example, 500% or more, preferably 700% or more, and more preferably 800% or more. This can improve the high elasticity and durability of the molded article. On the other hand, the upper limit of the elongation at break of the elastomer layer is not particularly limited, but may be, for example, 2000% or less, 1800% or less, or 1500% or less. This can improve the mechanical strength of the molded article.
[0034] The lower limit of the tear strength of the elastomer layer according to the present embodiment, measured in accordance with JIS K6252 (2001), is, for example, 25 N / mm or more, preferably 30 N / mm or more, more preferably 33 N / mm or more, and even more preferably 35 N / mm or more. This can improve the scratch resistance and mechanical strength of the molded article. In addition, the durability of the molded article during repeated use can be improved. On the other hand, the upper limit of the tear strength of the elastomer layer is not particularly limited, but may be, for example, 70 N / mm or less, or 60 N / mm or less. This can balance the various properties of the elastomer layer.
[0035] The lower limit of the tensile strength of the elastomer layer according to the present embodiment, measured in accordance with JIS K6251 (2004), is, for example, 6.0 MPa or more, preferably 7.0 MPa or more, and more preferably 8.0 MPa or more. This can improve the mechanical strength of the molded article. Also, the breaking energy can be increased. Therefore, a molded article having excellent durability and capable of withstanding repeated deformation can be realized. On the other hand, the upper limit of the tensile strength of the elastomer layer is not particularly limited, but may be, for example, 15 MPa or less, or 13 MPa or less. This can improve the operability of the molded article.
[0036] The upper limit of the durometer hardness A of the elastomer layer according to the present embodiment, as defined in accordance with JIS K6253 (1997), is, for example, 40.0 or less, preferably 39.0 or less, more preferably 38.0 or less, and even more preferably 35.0 or less. This can improve the flexibility of the molded article, and can realize a molded article with excellent deformability, which is easily deformed by bending or stretching. This can improve the operability of the molded article. The lower limit of the durometer hardness A of the elastomer layer is not particularly limited, and can be, for example, 1 or more, 5 or more, or 10 or more. This can increase the mechanical strength of the molded article.
[0037] The tensile stress M of the elastomer layer of the present embodiment measured in accordance with JIS K6251 (2004) at 25°C when the elastomer layer is stretched to 100% 100 The upper limit of the tensile stress M may be, for example, 3.0 MPa or less, preferably 2.0 MPa or less, more preferably 1.5 MPa or less, and further preferably 1.2 MPa or less. This can improve the ease of deformation of the elastomer. 100 The lower limit of the elastic modulus is not particularly limited, but may be 0.1 MPa or more, and preferably 0.3 MPa or more, which can improve the mechanical strength of the elastomer.
[0038] The tensile stress M of the elastomer layer of the present embodiment measured in accordance with JIS K6251 (2004) at 25°C when the elastomer layer is stretched by 300% 300 The upper limit of the tensile stress M may be, for example, 5.0 MPa or less, preferably 4.5 MPa or less, more preferably 4.0 MPa or less, and further preferably 3.5 MPa or less. This can improve the ease of deformation of the elastomer. 300 The lower limit of the elastic modulus is not particularly limited, but may be 0.5 MPa or more, and preferably 1.0 MPa or more, which can improve the mechanical strength of the elastomer.
[0039] In this embodiment, the above surface roughness, tack peak value, dynamic friction coefficient, breaking elongation, tensile strength, tear strength, and hardness can be controlled by appropriately selecting, for example, the type and amount of each component contained in the elastomer layer, the method for preparing the composition for forming the elastomer layer, the method for producing the elastomer layer, etc. Among these, for example, physically imparting unevenness to the elastomer layer, adjusting the surface roughness Ra of the unevenness transfer film, not forming a coating layer made of a slippage imparting agent on the surface of the elastomer layer, appropriately controlling the type and blending ratio of the resin constituting the elastomer layer, the crosslinking density and crosslinking structure of the resin, and improving the blending ratio of the inorganic filler and the dispersibility of the inorganic filler are listed as elements for setting the above surface roughness, tack peak value, dynamic friction coefficient, breaking elongation, tensile strength, tear strength, and hardness in the desired numerical range.
[0040] Next, the composition of the elastomer layer according to this embodiment will be described.
[0041] The elastomer constituting the elastomer layer may include, for example, one or more selected from the group consisting of silicone rubber, fluororubber, nitrile rubber, acrylic rubber, styrene rubber, chloroprene rubber, ethylene propylene rubber, urethane rubber, isoprene rubber, and natural rubber. These may be used alone or in combination of two or more.
[0042] Among these, silicone rubber can be used from the viewpoint of balance of rubber properties, chemical stability, and excellent thermal stability.
[0043] The thermosetting elastomer may be a cured product of a curable elastomer composition, and the silicone rubber may be a cured product of a silicone rubber-based curable composition.
[0044] The elastomer of the present embodiment may contain any component capable of exerting various functions. For example, from the viewpoint of increasing mechanical strength, the elastomer may contain an inorganic filler. As the inorganic filler, a known inorganic filler may be used, for example, silica particles may be used.
[0045] Hereinafter, a case will be described in which a silicone rubber-based hardening composition is used as the silicone rubber, which is an example of the elastomer of this embodiment.
[0046] The silicone rubber-based hardening composition of the present embodiment may contain a vinyl group-containing organopolysiloxane (A). The vinyl group-containing organopolysiloxane (A) is a polymer that is the main component of the silicone rubber-based hardening composition of the present embodiment.
[0047] The vinyl group-containing organopolysiloxane (A) can contain a vinyl group-containing linear organopolysiloxane (A1) having a linear structure.
[0048] The vinyl group-containing linear organopolysiloxane (A1) has a linear structure and contains vinyl groups, and these vinyl groups become crosslinking points during curing.
[0049] The vinyl group content of the vinyl group-containing linear organopolysiloxane (A1) is not particularly limited, but for example, it is preferable that the vinyl group content is 15 mol% or less, and more preferably 0.01 to 12 mol%, and that the vinyl group content is two or more in the molecule. This optimizes the amount of vinyl groups in the vinyl group-containing linear organopolysiloxane (A1), and ensures the formation of a network with each component described below. In this embodiment, "to" means that the numerical values at both ends are included.
[0050] In this specification, the vinyl group content refers to the mol % of vinyl group-containing siloxane units when all units constituting the vinyl group-containing linear organopolysiloxane (A1) are taken as 100 mol %, where it is considered that there is one vinyl group per vinyl group-containing siloxane unit.
[0051] The degree of polymerization of the vinyl group-containing linear organopolysiloxane (A1) is not particularly limited, but is, for example, preferably within the range of about 1000 to 10000, and more preferably about 2000 to 5000. The degree of polymerization can be determined, for example, as the polystyrene-equivalent number average degree of polymerization (or number average molecular weight) measured by GPC (gel permeation chromatography) using chloroform as a developing solvent.
[0052] Furthermore, the specific gravity of the vinyl group-containing linear organopolysiloxane (A1) is not particularly limited, but is preferably in the range of about 0.9 to 1.1.
[0053] By using a vinyl group-containing linear organopolysiloxane (A1) having a degree of polymerization and specific gravity within the above ranges, it is possible to improve the heat resistance, flame retardancy, chemical stability, etc. of the resulting silicone rubber.
[0054] As the vinyl group-containing linear organopolysiloxane (A1), those having a structure represented by the following formula (1) are particularly preferred.
[0055] [ka]
[0056] In formula (1), R 1is a substituted or unsubstituted alkyl group, alkenyl group, aryl group, or a hydrocarbon group consisting of a combination thereof, each having 1 to 10 carbon atoms. Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, and a propyl group, with a methyl group being preferred. Examples of the alkenyl group having 1 to 10 carbon atoms include a vinyl group, an allyl group, and a butenyl group, with a vinyl group being preferred. Examples of the aryl group having 1 to 10 carbon atoms include a phenyl group.
[0057] Also, R 2 is a substituted or unsubstituted alkyl group, alkenyl group, aryl group, or a hydrocarbon group consisting of a combination thereof, each having 1 to 10 carbon atoms. Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, and a propyl group, and among these, a methyl group is preferable. Examples of the alkenyl group having 1 to 10 carbon atoms include a vinyl group, an allyl group, and a butenyl group. Examples of the aryl group having 1 to 10 carbon atoms include a phenyl group.
[0058] Also, R 3 is a substituted or unsubstituted alkyl group having 1 to 8 carbon atoms, an aryl group, or a hydrocarbon group consisting of a combination thereof. Examples of the alkyl group having 1 to 8 carbon atoms include a methyl group, an ethyl group, and a propyl group, and among these, a methyl group is preferable. Examples of the aryl group having 1 to 8 carbon atoms include a phenyl group.
[0059] Furthermore, R in formula (1) 1 and R 2 Examples of the substituent of R include a methyl group and a vinyl group. 3 Examples of the substituent include a methyl group.
[0060] In addition, in formula (1), multiple R 1 are independent of each other and may be different or the same. 2 , and R 3 The same applies to.
[0061] Furthermore, m and n are the numbers of repeating units constituting the vinyl group-containing linear organopolysiloxane (A1) represented by formula (1), where m is an integer of 0 to 2000 and n is an integer of 1000 to 10000. m is preferably 0 to 1000 and n is preferably 2000 to 5000.
[0062] A specific example of the structure of the vinyl group-containing linear organopolysiloxane (A1) represented by formula (1) is that represented by the following formula (1-1).
[0063] [ka]
[0064] In formula (1-1), R 1 and R 2 are each independently a methyl group or a vinyl group, and at least one of them is a vinyl group.
[0065] Furthermore, the vinyl group-containing linear organopolysiloxane (A1) preferably contains a first vinyl group-containing linear organopolysiloxane (A1-1) having two or more vinyl groups in the molecule and a vinyl group content of 0.4 mol% or less, and a second vinyl group-containing linear organopolysiloxane (A1-2) having a vinyl group content of 0.5 to 15 mol%. By combining the first vinyl group-containing linear organopolysiloxane (A1-1) having a general vinyl group content as a raw rubber that is a raw material for silicone rubber, and the second vinyl group-containing linear organopolysiloxane (A1-2) having a high vinyl group content, the vinyl groups can be unevenly distributed, and the crosslinking density can be more effectively formed in the crosslinked network of the silicone rubber. As a result, the tear strength of the silicone rubber can be more effectively increased.
[0066] Specifically, the vinyl group-containing linear organopolysiloxane (A1) may be, for example, a vinyl group-containing linear organopolysiloxane represented by the above formula (1-1), 1 is a vinyl group and / or R2 a first vinyl group-containing linear organopolysiloxane (A1-1) having two or more units in the molecule each of which is a vinyl group and containing 0.4 mol % or less of a unit represented by R 1 is a vinyl group and / or R 2 It is preferable to use a second vinyl group-containing linear organopolysiloxane (A1-2) containing 0.5 to 15 mol % of units in which the vinyl group is present.
[0067] The first vinyl group-containing linear organopolysiloxane (A1-1) preferably has a vinyl group content of 0.01 to 0.2 mol %, and the second vinyl group-containing linear organopolysiloxane (A1-2) preferably has a vinyl group content of 0.8 to 12 mol %.
[0068] Furthermore, when the first vinyl group-containing linear organopolysiloxane (A1-1) and the second vinyl group-containing linear organopolysiloxane (A1-2) are combined and blended, the ratio of (A1-1) to (A1-2) is not particularly limited, but for example, the weight ratio of (A1-1):(A1-2) is preferably 50:50 to 95:5, and more preferably 80:20 to 90:10.
[0069] The first and second vinyl group-containing linear organopolysiloxanes (A1-1) and (A1-2) may each be used alone or in combination of two or more.
[0070] The vinyl group-containing organopolysiloxane (A) may also contain a vinyl group-containing branched organopolysiloxane (A2) having a branched structure.
[0071] <<Organohydrogenpolysiloxane (B)>> The silicone rubber-based hardenable composition of this embodiment can contain an organohydrogenpolysiloxane (B). The organohydrogenpolysiloxane (B) is classified into a linear organohydrogenpolysiloxane (B1) having a linear structure and a branched organohydrogenpolysiloxane (B2) having a branched structure, and may contain either one or both of these.
[0072] The linear organohydrogenpolysiloxane (B1) has a linear structure and a structure in which hydrogen is directly bonded to Si (≡Si-H), and is a polymer that undergoes a hydrosilylation reaction with the vinyl groups of the vinyl group-containing organopolysiloxane (A) and with vinyl groups of components blended into the silicone rubber-based curable composition, thereby crosslinking these components.
[0073] The molecular weight of the linear organohydrogenpolysiloxane (B1) is not particularly limited, but for example, the weight average molecular weight is preferably 20,000 or less, and more preferably 1,000 or more and 10,000 or less.
[0074] The weight average molecular weight of the linear organohydrogenpolysiloxane (B1) can be measured, for example, by polystyrene conversion in gel permeation chromatography (GPC) using chloroform as a developing solvent.
[0075] Furthermore, it is usually preferred that the linear organohydrogenpolysiloxane (B1) does not have a vinyl group, which can reliably prevent the crosslinking reaction from proceeding within the molecule of the linear organohydrogenpolysiloxane (B1).
[0076] As the linear organohydrogenpolysiloxane (B1) as described above, for example, one having a structure represented by the following formula (2) is preferably used.
[0077] [ka]
[0078] In formula (2), R4 is a substituted or unsubstituted alkyl group, alkenyl group, aryl group, a hydrocarbon group combining these groups, or a hydride group having 1 to 10 carbon atoms. Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, a propyl group, etc., and among these, a methyl group is preferable. Examples of the alkenyl group having 1 to 10 carbon atoms include a vinyl group, an allyl group, a butenyl group, etc. Examples of the aryl group having 1 to 10 carbon atoms include a phenyl group.
[0079] Also, R 5 is a substituted or unsubstituted alkyl group, alkenyl group, aryl group, a hydrocarbon group combining these groups, or a hydride group having 1 to 10 carbon atoms. Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, and a propyl group, and among these, a methyl group is preferable. Examples of the alkenyl group having 1 to 10 carbon atoms include a vinyl group, an allyl group, and a butenyl group. Examples of the aryl group having 1 to 10 carbon atoms include a phenyl group.
[0080] In addition, in formula (2), multiple R 4 are independent of each other and may be different or the same. 5 The same applies to R. 4 and R 5 At least two of these are hydride groups.
[0081] Also, R 6 is a substituted or unsubstituted alkyl group having 1 to 8 carbon atoms, an aryl group, or a hydrocarbon group combining these. Examples of the alkyl group having 1 to 8 carbon atoms include a methyl group, an ethyl group, and a propyl group, and among these, a methyl group is preferable. Examples of the aryl group having 1 to 8 carbon atoms include a phenyl group. 6 are independent of each other and may be different from each other or may be the same.
[0082] In addition, R in formula (2) 4 ,R 5 ,R6 Examples of the substituent include a methyl group and a vinyl group, and from the viewpoint of preventing an intramolecular crosslinking reaction, a methyl group is preferred.
[0083] Furthermore, m and n are the numbers of repeating units constituting the linear organohydrogenpolysiloxane (B1) represented by formula (2), where m is an integer of 2 to 150 and n is an integer of 2 to 150. Preferably, m is an integer of 2 to 100 and n is an integer of 2 to 100.
[0084] The linear organohydrogenpolysiloxane (B1) may be used alone or in combination of two or more kinds.
[0085] Since the branched organohydrogenpolysiloxane (B2) has a branched structure, it forms regions with high crosslink density, and is a component that greatly contributes to the formation of a sparsely-dense structure of crosslink density in the silicone rubber system. Also, like the linear organohydrogenpolysiloxane (B1), it has a structure in which hydrogen is directly bonded to Si (≡Si-H), and undergoes a hydrosilylation reaction with the vinyl groups of the vinyl group-containing organopolysiloxane (A) and with the vinyl groups of the components blended in the silicone rubber-based hardening composition, forming a polymer that crosslinks these components.
[0086] The specific gravity of the branched organohydrogenpolysiloxane (B2) is in the range of 0.9 to 0.95.
[0087] Furthermore, it is usually preferred that the branched organohydrogenpolysiloxane (B2) does not have a vinyl group, which can reliably prevent the crosslinking reaction from proceeding within the molecule of the branched organohydrogenpolysiloxane (B2).
[0088] As the branched organohydrogenpolysiloxane (B2), one represented by the following average composition formula (c) is preferred.
[0089] Average composition formula (c) (Ha (R 7 ) 3-a SiO 1 / 2 ) m (SiO 4 / 2 ) n (In formula (c), R 7 is a monovalent organic group, a is an integer ranging from 1 to 3, and m is H a (R 7 ) 3-a SiO 1 / 2 The number of units, n, is SiO 4 / 2 (the number of units)
[0090] In formula (c), R 7 is a monovalent organic group, preferably a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, an aryl group, or a hydrocarbon group consisting of a combination thereof. Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, and a propyl group, and among these, a methyl group is preferred. Examples of the aryl group having 1 to 10 carbon atoms include a phenyl group.
[0091] In formula (c), a is the number of hydride groups (hydrogen atoms directly bonded to Si) and is an integer ranging from 1 to 3, and preferably 1.
[0092] In addition, in formula (c), m is H a (R 7 ) 3-a SiO 1 / 2 The number of units, n, is SiO 4 / 2 It is the number of units.
[0093] The branched organohydrogenpolysiloxane (B2) has a branched structure. The linear organohydrogenpolysiloxane (B1) and the branched organohydrogenpolysiloxane (B2) differ in that their structures are linear or branched, and the number of alkyl groups R bonded to Si (R / Si) when the number of Si is 1 is in the range of 1.8 to 2.1 for the linear organohydrogenpolysiloxane (B1) and 0.8 to 1.7 for the branched organohydrogenpolysiloxane (B2).
[0094] Since the branched organohydrogenpolysiloxane (B2) has a branched structure, for example, when heated in a nitrogen atmosphere to 1000° C. at a heating rate of 10° C. / min, the amount of residue is 5% or more. In contrast, since the linear organohydrogenpolysiloxane (B1) is linear, the amount of residue after heating under the above conditions is almost zero.
[0095] Specific examples of the branched organohydrogenpolysiloxane (B2) include those having a structure represented by the following formula (3).
[0096] [ka]
[0097] In formula (3), R 7 R is a substituted or unsubstituted alkyl group having 1 to 8 carbon atoms, an aryl group, or a hydrocarbon group combining these, or a hydrogen atom. Examples of the alkyl group having 1 to 8 carbon atoms include a methyl group, an ethyl group, and a propyl group, and among these, a methyl group is preferable. Examples of the aryl group having 1 to 8 carbon atoms include a phenyl group. 7 Examples of the substituent include a methyl group.
[0098] In addition, in formula (3), multiple R 7 are independent of each other and may be different from each other or may be the same.
[0099] In addition, in formula (3), "-O-Si≡" indicates that Si has a branched structure extending three-dimensionally.
[0100] The branched organohydrogenpolysiloxane (B2) may be used alone or in combination of two or more kinds.
[0101] In addition, the amount of hydrogen atoms (hydride groups) directly bonded to Si in the linear organohydrogenpolysiloxane (B1) and the branched organohydrogenpolysiloxane (B2) is not particularly limited. However, in the silicone rubber-based curable composition, the total amount of hydride groups in the linear organohydrogenpolysiloxane (B1) and the branched organohydrogenpolysiloxane (B2) is preferably 0.5 to 5 moles, more preferably 1 to 3.5 moles, per mole of vinyl group in the vinyl group-containing linear organopolysiloxane (A1). This ensures that a crosslinked network is formed between the linear organohydrogenpolysiloxane (B1) and the branched organohydrogenpolysiloxane (B2) and the vinyl group-containing linear organopolysiloxane (A1).
[0102] <<Silica particles (C)>> The silicone rubber-based hardenable composition of this embodiment may contain silica particles (C).
[0103] The silica particles (C) are not particularly limited, but for example, fumed silica, calcined silica, precipitated silica, etc. These may be used alone or in combination of two or more kinds.
[0104] The silica particles (C) have a specific surface area, as measured by the BET method, of, for example, 50 to 400 m 2 / g, and 100 to 400m 2 / g is more preferable. Furthermore, the average primary particle size is, for example, preferably 1 to 100 nm, and more preferably about 5 to 20 nm.
[0105] By using silica particles (C) having a specific surface area and average particle size within this range, it is possible to improve the hardness and mechanical strength, particularly the tensile strength, of the silicone rubber that is formed.
[0106] <<Silane coupling agent (D)>> The silicone rubber-based hardenable composition of this embodiment may contain a silane coupling agent (D). The silane coupling agent (D) may have a hydrolyzable group. The hydrolyzable group is hydrolyzed by water to become a hydroxyl group, and the hydroxyl group undergoes a dehydration condensation reaction with the hydroxyl group on the surface of the silica particles (C), thereby modifying the surface of the silica particles (C).
[0107] In addition, the silane coupling agent (D) may contain a silane coupling agent having a hydrophobic group. This provides the surface of the silica particles (C) with this hydrophobic group, so that the cohesive force of the silica particles (C) in the silicone rubber-based curable composition and in the silicone rubber is reduced (there is less cohesion due to hydrogen bonds caused by silanol groups), and as a result, it is presumed that the dispersibility of the silica particles in the silicone rubber-based curable composition is improved. This increases the interface between the silica particles and the rubber matrix, and enhances the reinforcing effect of the silica particles. Furthermore, it is presumed that the slipperiness of the silica particles in the matrix is improved during deformation of the rubber matrix. And, due to the improvement in the dispersibility and slipperiness of the silica particles (C), the mechanical strength (for example, tensile strength, tear strength, etc.) of the silicone rubber due to the silica particles (C) is improved.
[0108] Furthermore, the silane coupling agent (D) may contain a silane coupling agent having a vinyl group. This allows the vinyl group to be introduced onto the surface of the silica particles (C). Therefore, when the silicone rubber-based curable composition is cured, that is, when the vinyl group of the vinyl group-containing organopolysiloxane (A) and the hydride group of the organohydrogenpolysiloxane (B) undergo a hydrosilylation reaction to form a network (crosslinked structure), the vinyl group of the silica particles (C) also participates in the hydrosilylation reaction with the hydride group of the organohydrogenpolysiloxane (B), so that the silica particles (C) are also incorporated into the network. This allows the formed silicone rubber to have a low hardness and a high modulus.
[0109] As the silane coupling agent (D), a silane coupling agent having a hydrophobic group and a silane coupling agent having a vinyl group can be used in combination.
[0110] An example of the silane coupling agent (D) is one represented by the following formula (4).
[0111] Y n -Si-(X) 4-n (4) In the above formula (4), n represents an integer of 1 to 3. Y represents any functional group having a hydrophobic group, a hydrophilic group, or a vinyl group, and when n is 1, it is a hydrophobic group, and when n is 2 or 3, at least one of them is a hydrophobic group. X represents a hydrolyzable group.
[0112] The hydrophobic group is an alkyl group having 1 to 6 carbon atoms, an aryl group, or a hydrocarbon group formed by combining these groups, and examples thereof include a methyl group, an ethyl group, a propyl group, and a phenyl group, with a methyl group being particularly preferred.
[0113] In addition, the hydrophilic group may be, for example, a hydroxyl group, a sulfonic acid group, a carboxyl group, or a carbonyl group, and among these, a hydroxyl group is particularly preferred. Note that, although a hydrophilic group may be included as a functional group, it is preferable that the hydrophilic group is not included from the viewpoint of imparting hydrophobicity to the silane coupling agent (D).
[0114] Further, examples of the hydrolyzable group include alkoxy groups such as methoxy and ethoxy groups, chloro groups, and silazane groups. Among these, silazane groups are preferred because of their high reactivity with the silica particles (C). In addition, those having a silazane group as a hydrolyzable group can be easily obtained by adding (Y n -Si-) structures.
[0115] Specific examples of the silane coupling agent (D) represented by the above formula (4) include, for example, alkoxysilanes such as methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, and decyltrimethoxysilane; chlorosilanes such as methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, and phenyltrichlorosilane; and hexamethyldisilazane, which have a hydrophobic group as a functional group. Examples of the silane having a vinyl group include alkoxysilanes such as methacryloxypropyltriethoxysilane, methacryloxypropyltrimethoxysilane, methacryloxypropylmethyldiethoxysilane, methacryloxypropylmethyldimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, and vinylmethyldimethoxysilane; chlorosilanes such as vinyltrichlorosilane and vinylmethyldichlorosilane; and divinyltetramethyldisilazane. Among these, taking into consideration the above description, it is particularly preferable that the silane having a hydrophobic group is hexamethyldisilazane, and the silane having a vinyl group is divinyltetramethyldisilazane.
[0116] <<Platinum or platinum compounds (E)>> The silicone rubber-based hardenable composition of this embodiment may contain platinum or a platinum compound (E). Platinum or a platinum compound (E) is a catalytic component that acts as a catalyst during curing. The amount of platinum or a platinum compound (E) added is a catalytic amount.
[0117] As the platinum or platinum compound (E), known substances can be used, such as platinum black, platinum supported on silica or carbon black, chloroplatinic acid or an alcohol solution of chloroplatinic acid, a complex salt of chloroplatinic acid and an olefin, and a complex salt of chloroplatinic acid and a vinylsiloxane.
[0118] The platinum or platinum compound (E) may be used alone or in combination of two or more kinds.
[0119] <<Water(F)>> Furthermore, the silicone rubber-based hardening composition of this embodiment may contain water (F) in addition to the above components (A) to (E).
[0120] Water (F) functions as a dispersion medium for dispersing each component contained in the silicone rubber-based hardening composition, and is also a component that contributes to the reaction between the silica particles (C) and the silane coupling agent (D). Therefore, the silica particles (C) and the silane coupling agent (D) can be more reliably linked to each other in the silicone rubber, and uniform properties can be exhibited overall.
[0121] Furthermore, the silicone rubber-based hardening composition of this embodiment may contain, in addition to the above components (A) to (F), known additive components that are blended into silicone rubber-based hardening compositions. Examples include diatomaceous earth, iron oxide, zinc oxide, titanium oxide, barium oxide, magnesium oxide, cerium oxide, calcium carbonate, magnesium carbonate, zinc carbonate, glass wool, mica, etc. In addition, dispersants, pigments, dyes, antistatic agents, antioxidants, flame retardants, thermal conductivity improvers, etc. may be blended as appropriate.
[0122] In the silicone rubber-based hardening composition, the content ratio of each component is not particularly limited, but is set, for example, as follows.
[0123] In this embodiment, the upper limit of the content of the silica particles (C) may be, for example, 60 parts by weight or less, preferably 50 parts by weight or less, and more preferably 35 parts by weight or less, based on 100 parts by weight of the total amount of the vinyl group-containing organopolysiloxane (A). This allows the balance between tear strength and tensile permanent set to be achieved. The lower limit of the content of the silica particles (C) is not particularly limited, but may be, for example, 20 parts by weight or more, based on 100 parts by weight of the total amount of the vinyl group-containing organopolysiloxane (A).
[0124] The silane coupling agent (D) is preferably contained in an amount of, for example, 5 parts by weight or more and 100 parts by weight or less, and more preferably 5 parts by weight or more and 40 parts by weight or less, per 100 parts by weight of the vinyl group-containing organopolysiloxane (A). This can reliably improve the dispersibility of the silica particles (C) in the silicone rubber-based hardening composition.
[0125] The content of the organohydrogenpolysiloxane (B) is preferably, for example, 0.5 parts by weight or more and 20 parts by weight or less, and more preferably 0.8 parts by weight or more and 15 parts by weight or less, based on 100 parts by weight of the total amount of the vinyl group-containing organopolysiloxane (A), the silica particles (C), and the silane coupling agent (D). By keeping the content of (B) within the above range, a more effective curing reaction may be achieved.
[0126] The content of platinum or platinum compound (E) means the amount of catalyst, and can be set appropriately, but specifically, the amount of platinum group metal in this component is 0.01 to 1000 ppm by weight, preferably 0.1 to 500 ppm, relative to the total amount of vinyl group-containing organopolysiloxane (A), silica particles (C), and silane coupling agent (D). By making the content of platinum or platinum compound (E) equal to or greater than the lower limit, the obtained silicone rubber composition can be sufficiently cured. By making the content of platinum or platinum compound (E) equal to or less than the upper limit, the curing speed of the obtained silicone rubber composition can be improved.
[0127] Furthermore, when water (F) is contained, its content can be appropriately set, but specifically, for example, it is preferably in the range of 10 to 100 parts by weight, more preferably in the range of 30 to 70 parts by weight, relative to 100 parts by weight of the silane coupling agent (D). This makes it possible to more reliably proceed with the reaction between the silane coupling agent (D) and the silica particles (C).
[0128] <Silicone rubber manufacturing method> Next, a method for producing the silicone rubber of this embodiment will be described. In the method for producing the silicone rubber of this embodiment, a silicone rubber-based hardening composition is prepared, and the silicone rubber can be obtained by hardening the silicone rubber-based hardening composition. Details are provided below.
[0129] First, the components of the silicone rubber-based hardening composition are mixed uniformly using any kneading device to prepare the silicone rubber-based hardening composition.
[0130] [1] For example, a predetermined amount of vinyl group-containing organopolysiloxane (A), silica particles (C), and a silane coupling agent (D) are weighed out, and then kneaded using any kneading device to obtain a kneaded product containing these components (A), (C), and (D).
[0131] It is preferable to prepare this mixture by first kneading the vinyl-containing organopolysiloxane (A) with the silane coupling agent (D) and then kneading (mixing) the silica particles (C), which improves the dispersibility of the silica particles (C) in the vinyl-containing organopolysiloxane (A).
[0132] In addition, when obtaining this kneaded product, water (F) may be added to the kneaded product of the components (A), (C), and (D) as necessary, which allows the reaction between the silane coupling agent (D) and the silica particles (C) to proceed more reliably.
[0133] Furthermore, it is preferable that the kneading of each of the components (A), (C), and (D) is carried out through a first step of heating at a first temperature and a second step of heating at a second temperature. This allows the surface of the silica particles (C) to be surface-treated with the coupling agent (D) in the first step, and allows the by-products generated by the reaction between the silica particles (C) and the coupling agent (D) to be reliably removed from the kneaded product in the second step. After that, the component (A) may be added to the obtained kneaded product as necessary, and further kneaded. This allows the compatibility of the components in the kneaded product to be improved.
[0134] The first temperature is preferably, for example, about 40 to 120° C., and more preferably, for example, about 60 to 90° C. The second temperature is preferably, for example, about 130 to 210° C., and more preferably, for example, about 160 to 180° C.
[0135] Moreover, the atmosphere in the first step is preferably an inert atmosphere such as a nitrogen atmosphere, and the atmosphere in the second step is preferably a reduced pressure atmosphere.
[0136] Furthermore, the time for the first step is, for example, preferably about 0.3 to 1.5 hours, and more preferably about 0.5 to 1.2 hours, and the time for the second step is, for example, preferably about 0.7 to 3.0 hours, and more preferably about 1.0 to 2.0 hours.
[0137] By setting the above conditions for the first and second steps, the above effects can be obtained more significantly.
[0138] [2] Next, the organohydrogenpolysiloxane (B) and platinum or a platinum compound (E) are weighed out in predetermined amounts, and then the components (B) and (E) are kneaded into the mixture prepared in the above step [1] using any kneading device to obtain a silicone rubber-based curable composition. The obtained silicone rubber-based curable composition may be a paste containing a solvent.
[0139] In addition, when mixing the components (B) and (E), it is preferable to mix the mixture prepared in the above step [1] with the organohydrogenpolysiloxane (B) and the mixture prepared in the above step [1] with platinum or a platinum compound (E), and then mix the mixtures together. This allows the components (A) to (E) to be reliably dispersed in the silicone rubber-based curable composition without allowing the reaction between the vinyl group-containing organopolysiloxane (A) and the organohydrogenpolysiloxane (B) to proceed.
[0140] The temperature at which the components (B) and (E) are kneaded is, for example, preferably about 10 to 70°C, and more preferably about 25 to 30°C, as roll setting temperature.
[0141] Furthermore, the kneading time is, for example, preferably about 5 minutes to 1 hour, and more preferably about 10 to 40 minutes.
[0142] In the above steps [1] and [2], by setting the temperature within the above range, the progress of the reaction between the vinyl group-containing organopolysiloxane (A) and the organohydrogenpolysiloxane (B) can be more reliably prevented or inhibited. In addition, in the above steps [1] and [2], by setting the kneading time within the above range, the components (A) to (E) can be more reliably dispersed in the silicone rubber-based curable composition.
[0143] The kneading device used in each of steps [1] and [2] is not particularly limited, but for example, a kneader, a two-roll mill, a Banbury mixer (continuous kneader), a pressure kneader, etc. can be used.
[0144] In addition, a reaction inhibitor such as 1-ethynylcyclohexanol may be added to the kneaded mixture in step [2], which makes it possible to more effectively prevent or inhibit the progress of the reaction between the vinyl group-containing organopolysiloxane (A) and the organohydrogenpolysiloxane (B) even if the temperature of the kneaded mixture is set to a relatively high temperature.
[0145] [3] Next, the silicone rubber-based hardenable composition is hardened to form a silicone rubber.
[0146] In this embodiment, the curing process of the silicone rubber-based curable resin composition is carried out, for example, by heating at 100 to 250° C. for 1 to 30 minutes (first curing) and then post-baking at 200° C. for 1 to 4 hours (second curing). By going through the steps described above, the silicone rubber of the present embodiment is obtained.
[0147] As a result of the inventor's investigations, the following findings were obtained: It was found that reducing the amount of filler in silicone rubber can reduce the hardness and tensile stress, but on the other hand, the tear strength decreases, and the durability of the silicone rubber decreases.
[0148] As a result of intensive research, it was found that by appropriately selecting a resin composition such as vinyl group-containing organopolysiloxane (A), it is possible to control the uneven distribution of crosslinking density and crosslinking structure, and to increase the tear strength of silicone rubber while realizing low stress and low hardness in a wide strain range. It was also found that the tensile strength of silicone rubber can be increased. Although the detailed mechanism is unclear, it is believed that the combined use of a high vinyl group-containing organopolysiloxane and a low vinyl group-containing organopolysiloxane can control the uneven distribution of crosslinking structure, thereby increasing the tear strength of silicone rubber while reducing hardness. In this way, it is possible to increase the breaking energy of silicone rubber by increasing the tear strength while maintaining other physical properties.
[0149] In addition, in this embodiment, for example, by reducing the amount of filler, the tensile stress in the initial strain can be reduced, while the tensile stress in the later strain can be reduced by controlling the crosslink density of the resin and the uneven distribution of the crosslinked structure.
[0150] In this embodiment, for example, by appropriately selecting the type and amount of each component contained in the silicone rubber-based curable composition, the method for preparing the silicone rubber-based curable composition, the method for producing the silicone rubber, etc., it is possible to control the tensile stress, breaking energy, tensile strength, tear strength, and hardness. Among these, examples of factors for setting the tensile stress, breaking energy, tensile strength, tear strength, and hardness within the desired numerical range include the combined use of a low-vinyl-group-containing linear organopolysiloxane (A1-1) and a high-vinyl-group-containing linear organopolysiloxane (A1-2), the use of a vinyl-group-containing organopolysiloxane (A) having a vinyl group at its terminal to control the crosslink density of the resin and the uneven distribution of the crosslinked structure, as well as the timing of addition of the vinyl-group-containing organopolysiloxane (A), the blending ratio of the silica particles (C), surface modification of the silica particles (C) with a silane coupling agent (D), and the addition of water to more reliably promote the reaction between the silane coupling agent (D) and the silica particles (C).
[0151] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. EXAMPLES
[0152] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.
[0153] The raw material components used in the examples and comparative examples are shown below. (Vinyl-containing organopolysiloxane (A)) Low vinyl group-containing linear organopolysiloxane (A1-1): Vinyl group-containing dimethylpolysiloxane (structure represented by formula (1-1) and R 1 (Structure in which only the terminal is vinyl) High vinyl-containing linear organopolysiloxane (A1-2): Vinyl-containing dimethylpolysiloxane (having the structure represented by formula (1-1) and R 1 and R 2 is a vinyl group)
[0154] (Organohydrogenpolysiloxane (B)) Organohydrogenpolysiloxane (B): Momentive Corporation, "TC-25D" (Silica particles (C)) Silica particles (C): Silica particles (particle size 7 nm, specific surface area 300 m 2 / g), manufactured by Nippon Aerosil Co., Ltd., "AEROSIL300" (Silane coupling agent (D)) Silane coupling agent (D-1): Hexamethyldisilazane (HMDZ), manufactured by Gelst, "HEXAMETHYLDISILAZANE (SIH6110.1)" Silane coupling agent (D-2): Divinyltetramethyldisilazane, manufactured by Gelst, "1,3-DIVINYLTETRAMETHYLDISILAZANE (SID4612.0)" (Platinum or platinum compounds (E)) Platinum or platinum compounds (E): Platinum compounds, Momentive, "TC-25A"
[0155] (Synthesis of vinyl group-containing organopolysiloxane (A)) [Synthesis Scheme 1: Synthesis of low vinyl group-containing linear organopolysiloxane (A1-1)] A low-vinyl-group-containing linear organopolysiloxane (A1-1) was synthesized according to the following formula (5). That is, 74.7 g (252 mmol) of octamethylcyclotetrasiloxane and 0.1 g of potassium siliconate were placed in a 300 mL separable flask equipped with a cooling tube and stirring blade and replaced with Ar gas, and the temperature was raised and the mixture was stirred at 120° C. for 30 minutes. At this time, an increase in viscosity was confirmed. The mixture was then heated to 155° C. and stirred for 3 hours, after which 0.1 g (0.6 mmol) of 1,3-divinyltetramethyldisiloxane was added and the mixture was stirred at 155° C. for an additional 4 hours. After four hours, the mixture was diluted with 250 mL of toluene and then washed three times with water. The washed organic layer was washed several times with 1.5 L of methanol for reprecipitation purification, and the oligomer and polymer were separated. The resulting polymer was dried overnight at 60°C under reduced pressure to obtain a low-vinyl-group-containing linear organopolysiloxane (A1-1) (Mn = 2.2 × 10 5 , Mw=4,8×10 5 The vinyl group content calculated from H-NMR spectrum measurement was 0.04 mol %.
[0156] [ka]
[0157] [Synthesis Scheme 2: Synthesis of high vinyl group-containing linear organopolysiloxane (A1-2)] A linear organopolysiloxane (A1-2) with high vinyl content was synthesized as shown in formula (6) below by the same synthesis process as for (A1-1) above, except that 0.86 g (2.5 mmol) of 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane was used in addition to 74.7 g (252 mmol) of octamethylcyclotetrasiloxane. (Mn=2.3×10 5 , Mw=5,0×10 5 The vinyl group content calculated from H-NMR spectrum measurement was 0.93 mol %. [ka]
[0158] (Preparation of Silicone Rubber-Based Curable Composition) A silicone rubber-based hardening composition was prepared as follows: First, a mixture of 95% vinyl-containing organopolysiloxane (A), silane coupling agent (D), and water (F) was pre-kneaded in the proportions shown in Table 1, and then silica particles (C) were added to the mixture and further kneaded to obtain a kneaded product (silicone rubber compound). Here, the kneading after the addition of the silica particles (C) was carried out through a first step of kneading for 1 hour under conditions of 60 to 90°C in a nitrogen atmosphere for the coupling reaction, and a second step of kneading for 2 hours under conditions of 160 to 180°C in a reduced pressure atmosphere for the removal of the by-product (ammonia). Thereafter, the mixture was cooled, and the remaining 5% of the vinyl group-containing organopolysiloxane (A) was added in two portions and kneaded for 20 minutes. Next, 2.6 parts by weight of organohydrogenpolysiloxane (B) and 0.5 parts by weight of platinum or platinum compound (E) were added to 100 parts by weight of the obtained kneaded product (silicone rubber compound) and kneaded with a roll to obtain a silicone rubber-based hardening composition.
[0159] [Table 1]
[0160] [Comparative Example 1] (Preparation of "sheet-shaped silicone rubber") The obtained silicone rubber-based hardening composition was pressed at 170°C and 10 MPa for 10 minutes to form a sheet having a thickness of 1 mm, and was subjected to primary hardening. It was then heated at 200°C for 4 hours to perform secondary hardening, and a sheet-like silicone rubber (a hardened product of the silicone rubber-based hardening composition) was obtained. The obtained "sheet-like silicone rubber" was used as it was in Comparative Example 1.
[0161] [Examples 1 to 11] (Preparation of "sheet-shaped silicone rubber" with an uneven surface) First, as shown in FIG. 1, the obtained silicone rubber-based hardening composition was placed in the molding space between the upper mold 10 and the lower mold 20 so as to be sandwiched between the uneven surfaces (rough surfaces) of the uneven transfer films 30, 40 (uneven transfer films shown in Table 2). Then, the composition was pressed for 10 minutes under the same heating and pressurizing conditions as in Comparative Example 1, that is, at 170°C and 10 MPa, molded into a sheet shape with a thickness of 1 mm, and cured primarily, and then heated at 200°C for 4 hours for secondary curing, thereby obtaining a sheet-like silicone rubber (cured product of the silicone rubber-based hardening composition). The uneven transfer films 30, 40 were separated from the surface of the obtained sheet-like silicone rubber (elastomer 50) to obtain a "sheet-like silicone rubber" having an uneven surface.
[0162] [Table 2]
[0163] The surface roughness Ra (μm) of the concave-convex surface of the concave-convex transfer film in Table 2 was measured in the same manner as the surface roughness Ra described below.
[0164] The silicone rubber sheets (hereinafter referred to as "elastomer layers") obtained in the Comparative Examples and Examples were evaluated based on the following evaluation items.
[0165] (Surface roughness Ra) The surface roughness Ra of the obtained elastomer layer was measured using a Keyence VK-9700 laser microscope under the conditions of lens: magnification 20x, pitch: 0.2 μm. Next, the surface roughness Ra (μm) of the surface of the elastomer layer was measured under the conditions of measurement area: 300 μm × 300 μm in accordance with JIS B0601-2001 described in the analysis software VKanalyzer. The evaluation results are shown in Table 3.
[0166] (Tack peak value) The tack peak value was measured using a tackiness checker manufactured by Toyo Seiki Co., Ltd. The measurement mode used was a constant load mode, in which the probe was pressed to a set pressure value and the pressure value was maintained until a set time had elapsed. Specifically, the area is 150 mm 2 The flat surface of an aluminum probe having a flat surface of 12 N was brought into contact with the surface of the measurement sample (the obtained elastomer layer) under the conditions of a probe moving speed of 2.3 mm / sec, a probe pressure strength of 12 N, and a pressure time of 6 seconds, and the flat surface of the aluminum probe was peeled upward at a probe moving speed of 2.3 mm / sec. The tack peak value on the surface of the elastomer layer was measured five times by a probe tack test, and the average of the five measured values was taken as the above-mentioned tack peak value TP (N). The evaluation results are shown in Table 3.
[0167] (Kinematic friction coefficient) The dynamic friction coefficient on the surface of the obtained elastomer layer was measured against PP, which is assumed to be used in gaskets, in accordance with JIS K7125. The evaluation results are shown in Table 3.
[0168] (Hardness: Durometer hardness A) Six of the resulting 1 mm thick elastomer layers were laminated to prepare a 6 mm test piece. The Type A durometer hardness of the resulting test piece was measured in accordance with JIS K6253 (1997). Two samples were used, and measurements were performed for each sample (n=5), with the average value of 10 measurements being taken as the measured value. The evaluation results are shown in Table 3.
[0169] (tear strength) Using the obtained elastomer layer having a thickness of 1 mm, a crescent-shaped test piece was prepared in accordance with JIS K6252 (2001), and the tear strength of the obtained crescent-shaped test piece at 25°C was measured. The unit is N / mm. The measurement was performed on five samples, and the average value of the five was taken as the measured value. The evaluation results are shown in Table 3.
[0170] (Tensile strength) Using the obtained elastomer layer having a thickness of 1 mm, a dumbbell-shaped No. 3 test piece was prepared in accordance with JIS K6251 (2004), and the tensile strength of the obtained test piece at 25°C was measured. The unit is MPa. Three samples were used, and the average value of the three values was taken as the measured value.
[0171] (tensile stress) Using the obtained elastomer layer having a thickness of 1 mm, a dumbbell-shaped No. 3 test piece was prepared in accordance with JIS K6251 (2004), and the tensile stress M of the obtained dumbbell-shaped No. 3 test piece at 100% elongation at 25 ° C was measured. 100 , and the tensile stress at 300% elongation M 300 The unit is MPa. Three samples were used and the average of the three values was taken as the measured value. The evaluation results are shown in Table 3.
[0172] Using the obtained elastomer layer having a thickness of 1 mm, a dumbbell-shaped No. 3 test piece was prepared in accordance with JIS K6251 (2004), and the breaking elongation of the obtained dumbbell-shaped No. 3 test piece at 25°C was measured. The breaking elongation was calculated based on the formula: [chuck movement distance (mm)] ÷ [initial chuck distance (60 mm)] × 100. The unit is %. Three samples were tested, and the average of the three values was used as the measured value. The evaluation results are shown in Table 3.
[0173] [Table 3]
[0174] In Table 3, "measurable" for the dynamic friction coefficient means that in the above-mentioned method for measuring the dynamic friction coefficient, the sliding piece did not move relative to the surface of the sample (elastomer layer), and measurement was not possible.
[0175] <Slipperiness test 1> The obtained silicone rubber-based curable composition was cured at 170°C for 15 minutes and at 200°C for 4 hours to form a cylindrical member having a diameter of 29 mm and a thickness of 12.5 mm. During molding, the outer surface of this cylindrical member was given a surface irregularity having the surface roughness Ra shown in Table 4. The surface roughness Ra (μm) of the cylindrical member was measured by the same method as that for the surface roughness Ra described above. In Table 4, when molding the cylindrical part in Test 1, a mold with a smooth molding surface was used, and when molding the cylindrical parts in Tests 2 to 4, molds with different projections and recesses on the molding surface were used.
[0176] To verify the applicability to gaskets, the obtained cylindrical part (rubber part) was inserted into a cylindrical PP tube with an inner diameter of 29 mm using a rod-shaped jig, and the slipperiness of the cylindrical part's outer surface was evaluated. Those where strong resistance was felt during insertion and the rubber member did not slide were rated as ×, those where the rubber member was slidable but resistance was felt were rated as ○, and those where no resistance was felt during insertion were rated as ◎.
[0177] Tests 3 to 5, which had a surface roughness of Ra = 4.0 μm or more, had good slipperiness with no resistance felt during insertion. In addition, slipperiness was good even during repeated insertion. In test 2, in which the surface irregularities were Ra=1.0 μm or more and less than 4.0, the rubber member could be inserted, but some resistance was felt. On the other hand, in Test 1, in which the surface irregularities were less than Ra=1.0 μm, strong resistance was felt during insertion, and the rubber member could not be inserted.
[0178] [Table 4]
[0179] <Slipperiness test 2> A rubbing test was carried out by horizontally sliding the uneven surface of the elastomer layer of each of the Examples and Comparative Examples against the surface of a mating sheet material shown in Table 5 on a flat test table while they were in contact with each other, and the sheets were evaluated according to the following evaluation criteria. The evaluation results are shown in Table 5. Those where strong resistance was felt when rubbing and the elastomer layer did not slide were marked with ×, those where the elastomer layer slid but resistance was felt were marked with ◯, and those where no resistance was felt when rubbing were marked with ◎. As shown in Table 5, the "same type of sheet" was used as the plastic mating sheet material, and "SUS304" (stainless steel) was used as the metallic mating sheet material. In the case of "same kind of sheets", for example, two elastomer layers of Example 1 were prepared, and the uneven surfaces of the two elastomer layers of Example 1 were brought into contact with each other to carry out the above-mentioned rubbing test. The other Examples and Comparative Examples were also evaluated in the same manner.
[0180] [Table 5]
[0181] It was found that the elastomer layers of Examples 1 to 11 maintained their rubber properties (physical properties) and had excellent slip properties compared to Comparative Example 1. In particular, the results of the slip property test showed that the surfaces of the elastomer layers of Examples 6 to 11 had further improved slip properties compared to Examples 1 to 5. It is expected that molded articles including the elastomer layers of such examples will also exhibit good slip properties while maintaining the desired rubber properties of the elastomer layer. [Explanation of symbols]
[0182] 10 Upper mold 20 Lower mold 30,40 Texture transfer film 32 Surface 50 Elastomer 52 Surface
Claims
1. A molded article having an elastomer layer, A molded article, wherein the surface roughness Ra of at least one side of the elastomer layer is 1.05 μm or more.
2. The molded article according to claim 1, A molded article, wherein the tack peak value TP on the surface of the elastomer layer is 4N or less, as measured by the following measurement procedure. (Measurement Procedure) Area 150mm 2 The flat surface of an aluminum probe having a flat surface of 12 N was brought into contact with the surface of the elastomer layer, which was the measurement sample, under conditions of a probe moving speed of 2.3 mm / sec, a probe crimping strength of 12 N, and a crimping time of 6 seconds, and the flat surface of the aluminum probe was then peeled upward at a probe moving speed of 2.3 mm / sec. The tack peak value on the surface of the elastomer layer was measured five times by a probe tack test, and the average of the five measured values was defined as the tack peak value TP.
3. The molded article according to claim 1 or 2, A molded article, wherein the dynamic friction coefficient of the surface of the elastomer layer is 2.0 or less, as measured in accordance with JIS K7125.
4. The molded article according to any one of claims 1 to 3, A molded article, wherein the elongation at break of the elastomer layer is 500% or more and 2000% or less, as measured in accordance with JIS K6251 (2004).
5. The molded article according to any one of claims 1 to 4, A molded article, wherein the tear strength of the elastomer layer, measured in accordance with JIS K6252 (2001), is 25 N / mm or more.
6. The molded article according to any one of claims 1 to 5, The molded article, wherein the elastomer layer has a tensile strength of 6.0 MPa or more and 15 MPa or less, as measured in accordance with JIS K6251 (2004).
7. The molded article according to any one of claims 1 to 6, The molded article has a durometer hardness A of the elastomer layer, as defined in accordance with JIS K6253 (1997), of 40.0 or less.
8. The molded article according to any one of claims 1 to 7, The elastomer layer comprises at least one selected from the group consisting of silicone rubber, fluororubber, nitrile rubber, acrylic rubber, styrene rubber, chloroprene rubber, ethylene propylene rubber, urethane rubber, isoprene rubber, and natural rubber.
9. The molded article according to any one of claims 1 to 8, A molded article, wherein the surface of the elastomer layer is a non-coated surface on which no coating layer made of a slip property imparting agent is formed.
Citation Information
Patent Citations
Continuous preparation of rubber sheet of rubber-coated fabric having emboss in its surface
JP1987080024A
Silicone rubber sheet for thermally compressive bonding
JP2004273669A
Manufacturing method for rubber film composite material
JP2008120093A
Flexographic printing plate, method for producing the same, thin film, and method for producing liquid crystal display element
JP2009034913A
Method of forming convexoconcave to rubber surface
JP2014091294A